Rightness in Evalating Basra and Kufa’s Views in The Work Of Al _ Anbary, Al - Insaf Fi Masael Al - Khilaf (Journal of the College of Education for Women, 2019)
This paper deals with the Kufis and basris agreements in Abo Al _ Barakat Al _ anbary’swork “ Al- Insaf Fi Masael Al - Khilaf.It attempts to settle the disputes and find out the rightviews.The book presents the issnes that the two schools of Kufa and Basra dispute upon and try toevaluate them so as to support the correct ones .The present researcher has noticed that theauthor of the above work was not always right or accurate in picturing a number of issues asdisputable whereas they implicitly shared the same views .Accordingly ,this papor sheds lighton such cases and drew acadernic researchers, attention to the invalidity of Al –anbary’smisjudged views.